Aseptic Meningitis in Pediatrics: Epidemiologic Evaluation and Cerebrospinal Fluid Changes - Hatamian, B.; Fahimzad, A. (Iranian Journal of Child Neurology, 2009)
Objective This study aimed at investigating seasonal variation, clinical symptoms, and cerebrospinal fluid (CSF) changes in patients with aseptic meningitis admitted in Mofid hospital between 1995 and 1996. Materials & Methods A total of 63 children with aseptic meningitis were enrolled in the study. Their age, gender, season of the disease, etiology, clinical symptoms, CSF changes, and treatment were evaluated and documented. Data were analyzed using SPSS 11.5. Results The male to female ratio of the patients was 2.5 to 1, mean age being 6.5 years. The disease occurrence was most common in spring and summer, and the most common symptoms observed were fever (92.6%), followed by nausea and vomiting (88.88% and 68.25%), neck stiffness, neck stiffness (54%), seizure (19%), kernig sign (14.28%), Brudzinski's sign (11.11%), and 1.58% of the patients had history of head injury. Mean white blood cell count for CSF was 165/mm3 (range, 6 to 850/mm3), the common cells being mononuclear cells; mean red blood cell count was 538 (range, 0 to 8100/mm3); protein and glucose levels were within the normal ranges. Blood and CSF culture and CSF smear were negative. Prognosis was excellent and mean duration of recovery was 5 days (range, 2 to 18 days). Conclusion Although the clinical symptoms of aseptic meningitis are similar to those of bacterial meningitis, its prognosis is excellent. The CSF features can be used to diagnose the disease.